2012
DOI: 10.1159/000341590
|View full text |Cite
|
Sign up to set email alerts
|

Body Image in Patients with Posttraumatic Stress Disorder after Childhood Sexual Abuse and Co-Occurring Eating Disorder

Abstract: Background: Body image is a multidimensional construct with cognitive-affective, behavioral and perceptive components. Survivors of childhood sexual abuse report a disturbance of the cognitive-affective component of their body image but not of the perceptive component. It has not yet been examined whether and how the behavioral component is affected. Also, it is still unknown whether the disturbances might be due to the influence of co-occurring eating disorders. Sampling and Methods: The cognitive-affective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…These results confirm findings in earlier studies that trauma that trauma history is associated with both body satisfaction (Wenninger & Heiman, 1998) and body attitude (Dyer et al, 2013; Sack et al, 2010). Sack et al (2010) reported that women with a background of sexual trauma showed a significantly lower body attitude than non-sexually traumatized patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm findings in earlier studies that trauma that trauma history is associated with both body satisfaction (Wenninger & Heiman, 1998) and body attitude (Dyer et al, 2013; Sack et al, 2010). Sack et al (2010) reported that women with a background of sexual trauma showed a significantly lower body attitude than non-sexually traumatized patients.…”
Section: Discussionsupporting
confidence: 92%
“…Wenninger and Heiman (1998) reported that women who had been sexually abused in childhood ( n  = 57) scored significantly lower on perceived physical health and on the subscale sexual attractiveness of the Body-Esteem Scale (Franzoi & Shields, 1984) than the control sample ( n  = 47). Dyer et al (2013) studied differences in body attitude in a group of 84 females in treatment for PTSD related to childhood sexual abuse and in a control group of 53 healthy participants. They used the Dresden Body Image Questionnaire (DBIQ-35; Pöhlmann, Roth, Brähler, & Joraschky, 2014) to measure body attitude, and the Body Image Avoidance Questionnaire (BIAQ; Rosen, Srebnik, Saltzberg, & Wendt, 1991) to assess the frequency with which one engages in avoidance behaviours related to body experience.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is also important to notice that the greater endorsement of all MOODS-SR EB in L'Aquila survivors with PTSD with respect to those without, could suggest high rates of comorbidity with ED, as reported in previous studies (Gleaves et al, 1998;Reyes-Rodriguez et al, 2011). These symptoms, in fact, belong to the clinical picture of ED, like other eating symptoms that can often be found in subjects with PTSD: feeling guilty after overeating (Godfrey et al, 2013), eating in response to stress (Talbot et al, 2013), and impairment in behavioral component of body image (Dyer et al, 2013). Nevertheless, a major limitation of the present study is the lack of information on ED comorbidity, thus we cannot determine whether PTSD survivors presented a full-blown or sub-threshold comorbidity with EDs.…”
Section: Commentsmentioning
confidence: 56%
“…59,[65][66][67] If abuse and neglect create body shame and therefore motivate patients to undergo plastic surgery, as we postulate, several trauma-related phenomena that plastic surgeons observe could be better explained: patients are poor historians of their surgery and do not remember what they have been told 80 ; they dislike multiple body areas 55,56,81-84 ; they cannot remember or dissociate from their prior surgical complications and therefore cannot accurately assess surgical risks 85 ; they are inappropriately anxious, untrusting, and require endless reassurance 60,72,[86][87][88][89][90][91] ; they are compelled to undergo more surgery despite good outcomes ("compulsive reenactment") 72,78,92 ; they indulge in selfdestructive behavior 72 or substance abuse 72 ; they blame surgeon or staff for events that cannot be controlled ("scapegoating") 93 or put themselves unnecessarily at risk ("revictimization") 75 ; and they may claim that they have been mistreated or victimized by the surgeon. 58,59,[65][66][67][68]70,75,[94][95][96][97] It is easy to imagine how the tormenting cacophony of these memory and processing disturbances could create the behavior that we clinicians interpret as depressed or demanding conduct, and that gives secondary rhinoplasty patients such unflattering reputations.…”
Section: Discussionmentioning
confidence: 99%